Combatting the causes of inequality affecting young people across Europe - Stigendal, Mikael (Routledge, Taylor & Francis Group, 2018)
"Inequality is one of the most burning issues of our time, affecting young people in particular. What causes inequality? And how can actors at the local level combat the causes, not only the symptoms? By seeking to answer these questions, the book will contribute to this growing and transdisciplinary subject area by using mainly qualitative research and a perspective that integrates theory in every phase of the analysis. Drawing on cultural political economy, based on critical realism, the author claims that the most important causes of inequality are the ones inherent as potentials in capitalism and the capitalist type of state. Compared with the first post-war decades, these potential causes have been actualised differently since around 1980. They are also actualised differently across Europe. The book explores these differences concerning growth models and welfare regimes. In general, societies have developed into a new condition of social inclusion, which explains why many young people have become excluded. Societal borders have arisen in the cities, separating the winners and losers of inequality. As agents in social structures and contexts of meaning, we all contribute to exclude others and set the conditions for being included. However, there is always a discretion to make a difference. Using this discretion, local actors across Europe can combat the causes of inequality by adopting a potential-oriented approach; taking advantage of existing experience and knowledge among young people; and empowering them collectively together with the rest of us who wants to combat the causes of inequality by transforming society"--